A Clinical Guide to Occupational and Environmental Lung Diseases - Huang, Yuh-Chin T.; Ghio, Andrew J.; Maier, Lisa A. (Humana Press, 2012)
A Clinical Guide to Occupational and Environmental Lung Diseases delivers a concise compendium to the diagnosis and management of occupational and environmental lung diseases, incorporating evidence-based guidelines where available. Each chapter provides an updated review and a practical approach to different occupational and environmental lung diseases.  With rapidly changing technology, new conditions and exposures will undoubtedly emerge. Clinicians need to remain vigilant about assessing the potential link between lung diseases and environmental exposures, and this book provides a practical guide to recognize, diagnose, and prevent occupational and environmental lung diseases.  Written for practicing clinicians including internists, pulmonologists, and primary care providers, as well as industrial hygienists and environmental regulators, A Clinical Guide to Occupational and Environmental Lung Diseases is a timely and important new volume and an invaluable contribution to the literature
Keywords: Pneumology/Respiratory System; Internal Medicine; Respiratory organs-Diseases; Internal medicine